2001
DOI: 10.3354/dao045109
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of single-round polymerase chain reaction (PCR) and pepsin-trypsin digest (PTD) methods for detection of Myxobolus cerebralis

Abstract: Single-round polymerase chain reaction (PCR) and pepsin-trypsin digest (PTD) methods were compared for the detection of Myxobolus cerebralis. Parallel tests were conducted on a total of 1743 free-ranging and 400 hatchery-reared salmonids. Concurrent results were found in 84.6% of the free-ranging fish samples, and 83.5% of the hatchery samples. PCR identified M. cerebralis more frequently than did PTD, and did so in many geographic locations previously considered free of the parasite. Average myxospore count b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
40
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 14 publications
2
40
0
Order By: Relevance
“…Prior studies (Andree et al 1998, Antonio et al 1998, Baldwin & Myklebust 2002, Schisler et al 2001) have reported effective molecular methods for detecting Myxobolus cerebralis, but these tests provided no biological explanation for parasite activity during disease development. Using MyxSP-1 as the target gene, our real-time TaqMan PCR test detected protease transcription from early, intermediate, and late developmental stages of the parasite (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies (Andree et al 1998, Antonio et al 1998, Baldwin & Myklebust 2002, Schisler et al 2001) have reported effective molecular methods for detecting Myxobolus cerebralis, but these tests provided no biological explanation for parasite activity during disease development. Using MyxSP-1 as the target gene, our real-time TaqMan PCR test detected protease transcription from early, intermediate, and late developmental stages of the parasite (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Ten fish were sampled prior to exposure and individually tested for the presence of nucleic acid of the Myxobolus cerebralis parasite by a polymerase chain reaction (PCR) test (Andree et al 1998), modified as a single round procedure (Schisler et al 2001).…”
Section: Methodsmentioning
confidence: 99%
“…1986) and testing each individual T. tubifex was cost prohibitive. These composite samples were analyzed by a single-round polymerase chain reaction (PCR) assay described in Schisler et al (2001) to determine the presence of M. cerebralis DNA, using a modification of the technique described by Andree et al (1998).The proportion of infected Tubifex tubifex was calculated using composite sampling statistics (Zendt & Bergersen 2000). Infection rates were calculated using the equation given by Boswell & Patil (1987): where is the unknown prevalence of infection, n is the number of individuals per composite sample, m is the number of composite samples, and p m is the proportion of the composite samples that were positive for Myxobolus cerebralis DNA.…”
mentioning
confidence: 99%